2016
DOI: 10.3389/fphys.2016.00595
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adrenomedullin Results in Microbiota Changes and Aggravates Azoxymethane and Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: The link between intestinal inflammation, microbiota, and colorectal cancer is intriguing and the potential underlying mechanisms remain unknown. Here we evaluate the influence of adrenomedullin (AM) in microbiota composition and its impact on colitis with an inducible knockout (KO) mouse model for AM. Microbiota composition was analyzed in KO and wild type (WT) mice by massive sequencing. Colitis was induced in mice by administration of azoxymethane (AOM) followed by dextran sulfate sodium (DSS) in the drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…In addition, the genus Acinetobacter, one of the main genera of the Proteobacteria phyla to contribute to IBD disease activity [48], was significantly more abundant in IBD-PSC patients as compared to PSC patients without IBD. An increased abundance of Fusobacteriaceae, Stenotrophomonas and Micrococcus was seen in inflamed tissues, which is in accordance with previous investigations of IBD disease activity [49][50][51], while the found reduced levels of Bacteroidetes (phylum) and Caulobacterales (order) in inflamed tissue are consistent with mouse studies of colitis [52]. Thus, these findings are in line with previously published results for IBD and inflammation [53], indicating that the microbial signature present in the biopsies accurately represent disease state and that our sample is therefore useful for further exploration regarding rPSC.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the genus Acinetobacter, one of the main genera of the Proteobacteria phyla to contribute to IBD disease activity [48], was significantly more abundant in IBD-PSC patients as compared to PSC patients without IBD. An increased abundance of Fusobacteriaceae, Stenotrophomonas and Micrococcus was seen in inflamed tissues, which is in accordance with previous investigations of IBD disease activity [49][50][51], while the found reduced levels of Bacteroidetes (phylum) and Caulobacterales (order) in inflamed tissue are consistent with mouse studies of colitis [52]. Thus, these findings are in line with previously published results for IBD and inflammation [53], indicating that the microbial signature present in the biopsies accurately represent disease state and that our sample is therefore useful for further exploration regarding rPSC.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown a strong positive effect using AM as treatment for colitis symptoms in rodents 22 and humans 15 , 23 . Besides, this study shows that AM negative modulation by 16311 exacerbates colitis symptoms suggesting that AM prevents the symptoms of the disease in line with previous experiments 20 , 36 . Microscopic analysis of colonic sections confirmed data from macroscopic observations reflecting a tumor reduction in 145425-treated mice.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, AM and PAMP are antimicrobial peptides found in most epithelial surfaces and body secretions 24 , 25 and their presence or absence modifies the composition of gut microbiota 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, myeloperoxidase (MPO), reactive oxygen species (ROS) and nitric oxide (NO) are associated with the development of IBD. Notably, hAM treatment reduces TNFα, IL‐1β, and IL‐6 levels [Hayashi et al, ], and hAM‐knockout mice with DSS‐induced colitis had changes in gut microbiota populations and increased TNFα, IL‐1β, IL‐6, IL‐10, IL‐17 and IL‐22 mRNA expression [Martinez‐Herrero et al, ]. It can therefore be deduced that PEG‐hAM treatment inhibits production of these proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%